Influence of wood particle size on strength properties of wood plastics composite (Wpc) from laran species - Mohd Sukhairi Mat Rasat; Razak Wahab; Amran Shafie; Janshah Moktar; Mahani Yusoff; Zulhisyam Abdul Kari @ Abdullah; Sitti Fatimah Mhd. Ramle (AENSI, 2013)
Wood plastics composite (WPC) have seen a large growth in the worldwide in recent years. Wood and other biomass resources have been blended with thermoplastics such as polyethylene, polypropylene, polylactic acid and polyvinyl chloride to form WPC. In this work, the influence of wood particle size on strength properties of WPC from Laran species (Neolamarckia cadamba) would like to investigate. The wood particle from Laran species at size of 75 and 250 μm have been blended with polypropylene to produce the WPC. The WPC were produced from two types of ratio (10:90 and 30:70) between wood particle and polypropylene. The investigation was focused on the comparison between different wood particle size and ratio between wood particle and polypropylene. The strength properties were conducted in this research for static bending and tensile strength. The result showed that wood particle from 75 μm in geometry size with ratio of 30:70 between wood particle and polypropylene was most suitable in producing WPC. It was concreted by highest resulting for static bending and tensile strength that shown the WPC produced by 75 μm in geometry size of wood particle either for ratio of 30:70 or 10:90 between wood particle and polypropylene compare to the others. The geometry size of wood particle as well as the ratio was found to influence the strength properties of the WPC.